Endonasal Surgery after Cocaine Abuse: Safe at Any Interval? - L. K. Døsen; R. Haye (Case Reports in Otolaryngology)
Objective. We report a case of poor healing after endonasal surgery for nasal septal perforation ten years after cocaine abuse was ended. Method. The clinical findings are presented. Results. A 35-year-old man presented with a small nasal septal perforation caused by cocaine abuse. He had stopped using it ten years previously so surgery was considered safe. The perforation was surgically closed using an endonasal approach. The perforation, however, recurred, the incision healing delayed, and a saddle deformity developed. Conclusion. The effects of cocaine abuse seem to persist causing poor healing after nasal surgery. Prosthetic treatment should be the primary choice. Caution should be employed when considering surgery even in small perforations due to cocaine abuse even many years after the abuse was terminated.